2008
DOI: 10.1021/cc800118v
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Three-Step One-Pot Microwave-Assisted Synthesis of 2,5-Dioxo-1,2,5,6,7,8-hexahydro-3-quinolinecarbonitrile Library

Abstract: Many well-known drugs contain 2-pyridone and 2-quinolone scaffolds. In the current paper, a one-pot three-step microwave-assisted method for the synthesis of N1-substituted 2,5-dioxo-1,2,5,6,7,8-hexahydro-3-quinolinecarbonitrile derivatives was developed. Employing this protocol, we quickly generated 105 compounds library from 1,3-cyclohexanediones, dimethylformamide dimethylacetal, and various cyanacetamides.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(10 citation statements)
references
References 23 publications
0
10
0
Order By: Relevance
“…The use of piperidine as catalyst in i-PrOH under microwave irradiation at 100 ºC during 5 min [8] resulted in formation of pure expected product 8a, but the isolated yield was again very low (12%, Entry 9). Further experiments with catalytic amounts of piperidine, its stoichiometric quantities and excess at higher temperatures (Entries [10][11][12][13][14] showed that under such conditions increasing amounts of the undesired by-product 10a appeared in the isolated material. The reaction carried out at 160 °С during 20 min under microwave irradiation gave the pure by-product (10a, Entry 15).…”
Section: Search For Optimal Reaction Conditionsmentioning
confidence: 99%
See 2 more Smart Citations
“…The use of piperidine as catalyst in i-PrOH under microwave irradiation at 100 ºC during 5 min [8] resulted in formation of pure expected product 8a, but the isolated yield was again very low (12%, Entry 9). Further experiments with catalytic amounts of piperidine, its stoichiometric quantities and excess at higher temperatures (Entries [10][11][12][13][14] showed that under such conditions increasing amounts of the undesired by-product 10a appeared in the isolated material. The reaction carried out at 160 °С during 20 min under microwave irradiation gave the pure by-product (10a, Entry 15).…”
Section: Search For Optimal Reaction Conditionsmentioning
confidence: 99%
“…However, the formation of two different structures in the course of the above described reactions is possible following two alternative reaction mechanisms (Paths A and B, Scheme 4). In the earlier papers of our group [8,10] enamines 21 were shown to react with N-substituted cyanoacetamides 22 via intermediate formation of resonance-stabilized enolates 23 (Scheme 5) similarly to Path B (Scheme 4). The intermediates 23 were isolated as precipitates and their structure was defined in X-ray diffraction study [9].…”
Section: Determination Of the Product Structurementioning
confidence: 99%
See 1 more Smart Citation
“…5 additional diversity point into the final 2-pyridone molecule via the amide group 10 or, depending on the reaction conditions, leads to N1-substituted 3-cyano-2-pyridones. 11 In this work we aimed to investigate a novel interaction of N-substituted cyanoacetamides 1a-f with diethyl 2-(ethoxymethylene)malonate 12 (DEEMM) 2.…”
Section: Introductionmentioning
confidence: 99%
“…1 As a result, numerous annulation methods have been designed for its construction. 2,3 In this regard, we were attracted to the structure of lyconadin A (1, Fig. 1), a Lycopodium alkaloid with a unique pentacyclic skeleton that contains a 2-pyridone moiety.…”
Section: Introductionmentioning
confidence: 99%